One-pot synthesis of {Mo6I8}4+-doped polystyrene microspheres via a free radical dispersion copolymerisation reaction - Vorotnikova, Natalya A; Edeleva, Mariya V; Kurskaya, Olga G; Brylev, Konstantin A; Shestopalov, Alexander M; Mironov, Yuri V; Sutherland, Andrew J; Efremova, Olga A; Shestopalov, Michael A (Polymer International, 2017)
© 2017 Society of Chemical Industry Molybdenum octahedral clusters, when incorporated into an appropriate polymer matrix, are considered as promising agents for a range of biological applications. This work describes the one-pot synthesis, morphology and cellular toxicity of nano-sized polystyrene beads doped with luminescent cluster complexes [{Mo 6 X 8 }(NO 3 ) 6 ] 2− (X = Cl, Br or I). Specifically, the particles were obtained by free radical dispersion copolymerisation of styrene and methacrylic acid or 4-vinylpyridine in the presence of the cluster complexes. The effects of the cluster loading in the reaction mixture on both the content of the final material and number-average molar mass of the copolymers were evaluated. © 2017 Society of Chemical Industry.
Keywords: Polymers and Plastics